Design and implementation of an on-line oil palm fruit-harvesting robot - Lim, Yu Jian; Wan Ismail, Wan Ishak (Universiti Putra Malaysia, 1999)
This work present a concept robot designed and built for a new on-line oil palm fruit-harvesting strategy in highly unstructured environments, involving human-machine task distribution. The operator directs the robot arm to the Fresh Fruit Bunch (FFB) trough the Internet Super Highway with the help of wireless network devices and CCD communication camera. Computer verify the precise distance of the FFB and the cutting arm with the help of infra red range finder. Computer adequate cutting sequences and controls the motion of all the mechanical components.